Facilitated Reflective Performance Feedback: Developing an Evidence- and Theory-Based Model That Builds Relationship, Explores Reactions and Content, and Coaches for Performance Change (R2C2). (December 2015) - Sargeant, Joan; Lockyer, Jocelyn; Mann, Karen; Holmboe, Eric; Silver, Ivan; Armson, Heather; Driessen, Erik; MacLeod, Tanya; Yen, Wendy; Ross, Kathryn; Power, Mary
Abstract : Purpose: To develop and conduct feasibility testing of an evidence-based and theory-informed model for facilitating performance feedback for physicians so as to enhance their acceptance and use of the feedback. Method: To develop the feedback model (2011–2013), the authors drew on earlier research which highlights not only the factors that influence giving, receiving, accepting, and using feedback but also the theoretical perspectives which enable the understanding of these influences. The authors undertook an iterative, multistage, qualitative study guided by two recognized research frameworks: the UK Medical Research Council guidelines for studying complex interventions and realist evaluation. Using these frameworks, they conducted the research in four stages: (1) modeling, (2) facilitator preparation, (3) model feasibility testing, and (4) model refinement. They analyzed data, using content and thematic analysis, and used the findings from each stage to inform the subsequent stage. Results: Findings support the facilitated feedback model, its four phases—build r elationship, explore r eactions, explore c ontent, c oach for performance change (R2C2)—and the theoretical perspectives informing them. The findings contribute to understanding elements that enhance recipients' engagement with, acceptance of, and productive use of feedback. Facilitators reported that the model made sense and the phases generally flowed logically. Recipients reported that the feedback process was helpful and that they appreciated the reflection stimulated by the model and the coaching. Conclusions: The theory- and evidence-based reflective R2C2 Facilitated Feedback Model appears stable and helpful for physicians in facilitating their reflection on and use of formal performance assessment feedback. Abstract : Supplemental Digital Content is available in the text.